APPLICATION OF CASH WAQF SCHEME AS AN ALTERNATIVE WAY OF SUPPORTING UNDERPRIVILEGE - Yakubu, Aminu; Yakubu, Aminu; Aziz, Azreen Hamiza Abdul; Husseini, Yahya Alhaji; Wali, Fadimatu (IJRDO - Journal of Social Science and Humanities Research, 2022)
Privilege is a right or social advantage in society while the underprivileged are poor that have no social advantages in society. Some of the fundamental rights of all members of civilized society are denied to them because of their economic or social circumstances. This paper aimed at providing an alternative solution for supporting the underprivileged through the application of the cash waqf scheme. The study used a basic qualitative research design. The data collection method was conducted through interviews with five underprivileged from different categories. Thematic analysis was used to examine and analyze the responses of the informants using Atlas.ti v8.0 qualitative data analysis tool. The data reveal that those from lower socioeconomic status have fewer advantages, privileges, and opportunities than people from higher socioeconomic status. The findings also show a positive and reliable impact of cash waqf scheme application as an alternative and enduring solution for supporting underprivileged people. Therefore, there is a need to have a durable and reliable solution to cater to underprivileged people so that they can live their lives in a well-balanced society.